Tetrahedron. Issue 8 (28th June 2019) - Wu, Lin; Chen, Yusheng; Pei, Jingfang; Tang, Min; Wang, Shangshang; Liu, Zhichang
Abstract : Connecting a triangle base and an apex forms a simplest polyhedron—that is, a tetrahedron. On account of their structural simplicity and stability, two common classes of tetrahedra—namely, M4 L4 and M4 L6 (M indicates anions or metal cations, L indicates ligands with C 3 symmetry for M4 L4 and C 2 symmetry for M4 L6, respectively)—can be readily constructed from (i) six straight edges through an edge‐bridged strategy or (ii) four triangle faces through a face‐capped strategy, by means of supramolecular or coordination assembly. The intrinsic cavities inside tetrahedra enable them to act as versatile hosts for encapsulating a variety of guests, which leads to a wide range of applications including molecular recognition, catalysis, sensing and so on. In this review, we intend to summarize specifically the work carried out in the realm of porous tetrahedral cages. It includes representative synthetic strategies for the preparation of tetrahedra along with a general summary on their structural features. Thereafter, we will highlight the state‐of‐the‐art progress in various functions of tetrahedra, in addition to presenting a full overview of applications wherein we aim to provide new insights into the design and preparation of new topological geometric structures and functional materials on the basis of the simplest polyhedron—tetrahedron. Abstract : We summarize herein the structures, synthetic strategies, properties, and applications of two different classes of tetrahedral cages.